The blind spots of trade impact assessment: macroeconomic adjustment costs and the social costs of regulatory change - Werner Raza; Bernhard Tröster; Rudi von Arnim (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2016)
Economic studies on trade liberalization typically highlight positive expected effects. This paper discusses those issues which are frequently neglected, but are nevertheless important for policy-makers. These are macroeconomic adjustment costs and social costs of regulatory change. Our discussion uses the most relevant studies on the economic effects of the Transatlantic Trade and Investment Partnership (TTIP) as reference points. We provide a rough estimate of macroeconomic adjustment costs of TTIP in the order of exteuro33–60 billion over a 10-year transition period. Our analysis of regulatory change concludes that assessments have been biased and that the social costs of regulatory change due to TTIP might be substantial. Given the prominence of regulatory issues on the trade agenda, we call for full ex-ante regulatory impact assessment of future trade agreements.
Keywords: F13; F14; F17; 330; trade policy; trade impact assessment; non-tariff measures; macroeconomic adjustment costs; social costs